Theoretical and practical issues and challenges in takaful for construction works - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin (2015)
According to the Malaysia Economic Report 2015/2016, the construction industry of Malaysia is estimated to contribute some 8% to the nation’s GDP in year 2015. Consequently, activities related to construction are widespread, hence the potential of loss and damage they entail. Such potential loss and damage of construction works require protection and the most common type of insurance in compliance with the Shariah is Contractor’s All Risks (CAR) Takaful. The CAR Takaful continuously recorded significant performance with 15% increment yearly. Critically, despite substantial growth, the penetration of CAR Takaful industry is far below its potentials. A wide range of issues and challenges concerning construction takaful are being debated by Shariah scholars and technocrats. This chapter aims to review the theory and practice of takaful in general and CAR Takaful specifically, with the objective to provide better understanding of takaful and CAR Takaful and to highlight issues and challenges surrounding thereto. The outcome of the review suggests that the takaful and CAR Takaful are plagued with a host of theoretical and practical issues and challenges including the Shariah legitimacy in the practice of takaful and CAR Takaful, ambiguous regulatory framework, lack of transparency and accountability and issues related to governance. These issues and challenges require urgent attention or else they may not augur well for the future of the takaful and CAR Takaful industry.